Pengaruh Komunikasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT Nipsea Paint And Chemicals - Amelia Ramadanti; Sari Marliani; July Yuliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the global business world, companies are required to always improve their competitiveness, innovation, and “In the global business world, companies are required to always improve their competitiveness, innovation, and productivity. In this era of globalization, companies must be able to adapt to changes that occur rapidly in the global market. The purpose of this study is to determine the effect of communication and work environment on employee performance at PT Nipsea Paint and Chemicals. The study was conducted using quantitative research with descriptive and verification approaches. The population and sample of the study involved 80 respondents from PT Nipsea Paint and Chemicals, with a saturated sample method for sampling. Using a multiple linear regression analysis model to analyze data at a significance level of 5%. The results showed that the communication score of PT Nipsea Paint and Chemicals was 299.6 in the range of 261-342 with fairly good criteria. In the Work Environment it was 311.1 in the range of 261-342 with fairly good criteria. And the total Employee Performance score was 327.4 in the range of 261-342 with fairly good criteria. Partially, the Communication variable got a sig value. 0.043 < 0.05 and t count = 2.063 > t table = 1.990. The work environment variable partially gets a sig. value of 0.000 < 0.05, and t count = 4.438 > t table = 1.990. Communication and work environment have a simultaneous effect on employee performance, a sig. value of 0.000 < 0.05 and f count = 22.297 > f table = 3.12. The results of the determination coefficient test obtained an adjusted R-square value of 0.367 (36.7%). Showing that employee performance variables can be explained by communication and work environment variables by 36.7%, then the remaining value is 63.3% (100% - 36.7%) which explains other variables not examined in this study such as motivation, work discipline, compensation, work culture, commitment, and others